Rancang Bangun Dan Kinerja Alat Borazsilab Filter Dengan Sistem Filtrasi - Nitsae, Merpiseldin; Solle, Hartini R.L.; Blegur, Willem Amu; Solissa, Arfie Pigan (Jurnal Penelitian Hasil Hutan, 2023)
Research has been carried out on the BorazSiLab Filter design and performance used filtration system. The selected filtration mechanism is a multi-stage filtration system. The filter material used is lontar shell activated charcoal, coconut fiber, sand, and zeolite. The purpose of this study is to test the performance of the tool (effectiveness and efficiency) filled with the four materials above. The implementation stages of this research are divided into two, namely fabricating the BorazSiLab Filter tool and testing the reliability of tool. To facilitate tool fabrication, it is necessary to design tools in the form of working drawings of 2D shapes and 3D geometry so that they are easy to understand. The reliability test was carried out on the dimensions of the filter box, the surface area and volume of the material, the filtration discharge, and the water quality (pH, temperature, odor, and colors). The results showed that the tool was made of a glass box measuring 20×20×20 cm. The filtration time is fixed at 45 minutes. The measured filtration efficiency and effectiveness of the filter material surface area, filter media volume, filtration discharge before (Qin) and after (Qout) filtration are 0,0022 m2 (one tea bag) to 0,0044 m2 (two tea bag); 3,3×105 m3 (one tea bag) to 5,81×105 m3 (two tea bag); 1,1423 L/s; and 0,00046 L/s. Preliminary tests for water quality before and after for the parameters of odor, pH, and temperature values, respectively, are odor to odorless; colored to colorless pH = 7; temperature = 26,1 ± 3 °C to 27,9 ± 3 °C. Therefore, the BorazSiLab Filter can be used as a filtration tool for wastewater treatment.